Functional connectivity in complex regional pain syndrome: A bicentric study - Hok, Pavel; Strauss, Sebastian; McAuley, James; Domin, Martin; Wang, Audrey P; Rae, Caroline; Moseley, G Lorimer; Lotze, Martin (NeuroImage, 2024)
Brain imaging studies in complex regional pain syndrome (CRPS) have found mixed evidence for functional and structural changes in CRPS. In this cross-sectional study, we evaluated two patient cohorts from different centers and examined functional connectivity (rsFC) in 51 CRPS patients and 50 matched controls. rsFC was compared in predefined ROI pairs, but also in non-hypothesis driven analyses. Resting state (rs)fMRI changes in default mode network (DMN) and the degree rank order disruption index (kD) were additionally evaluated. Finally, imaging parameters were correlated with clinical severity and somatosensory function. Among predefined pairs, we found only weakly to moderately lower functional connectivity between the right nucleus accumbens and bilateral ventromedial prefrontal cortex in the infra-slow oscillations (ISO) band. The unconstrained ROI-to-ROI analysis revealed lower rsFC between the periaqueductal gray matter (PAG) and left anterior insula, and higher rsFC between the right sensorimotor thalamus and nucleus accumbens. In the correlation analysis, pain was positively associated with insulo-prefrontal rsFC, whereas sensorimotor thalamo-cortical rsFC was positively associated with tactile spatial resolution of the affected side. In contrast to previous reports, we found no group differences for kD or rsFC in the DMN, but detected overall lower data quality in patients. In summary, while some of the previous results were not replicated despite the larger sample size, novel findings from two independent cohorts point to potential down-regulated antinociceptive modulation by the PAG and increased connectivity within the reward system as pathophysiological mechanisms in CRPS. However, in light of the detected systematic differences in data quality between patients and healthy subjects, validity of rsFC abnormalities in CRPS should be carefully scrutinized in future replication studies.
Keywords: Female; lidé středního věku; Cross-Sectional Studies; Brain; konektom; mužské pohlaví; Default Mode Network; magnetická rezonanční tomografie; Humans; dospělí; komplexní regionální syndromy bolesti; nervová síť; Complex Regional Pain Syndromes; průřezové studie; CRPS; Connectome; lidé; Middle Aged; default mode network; mozek; Magnetic Resonance Imaging; Biomarker; Neuropathic pain; ženské pohlaví; Adult; Resting-state fMRI; Functional connectivity; Male; Nerve Net